Working Students: Educational Success and Subjective Well-being - N. A. Lyz’; O. N. Istratova; E. V. Golubeva (Высшее образование в России)
Recently, there has been an increase in the number of students who combine study with work. This requires special attention of universities to such students and updates the study of educational success factors. The study is relevant as considers working students as subjects of learning and life, from the standpoint of personal and professional development experience acquired at the university, involvement in the educational process, satisfaction with learning, and well-being.The purpose of the empirical study is to identify the features of educational experience, subjective well-being and self-change potential among working students. The study involves 290 students of bachelor and specialist programs from five universities. The sample includes students who work for more than half a year (N=95), work from time to time (N=90) and study only (N=105). The results showed that the educational experience is most formed among those students who combine their studies with work in the specialty which is being received at the university. Long-term and occasionally working students differ from non-working students by a higher desire to participate in developmental activities, confidence in their ability to successfully solve the problems of learning and social interaction, self-directed learning skills, tendency to analyze and self-control their learning.Also, working students are superior to those who are just studying in the self-change potential and the subjective well-being level. It is concluded that the success and well-being of working students are largely determined by their resources of subjectness and aspiration for development. This allows them to function successfully, combining educational and labor activities as two areas of experience accumulation. Directions for improving university practice in terms of creating conditions for the educational success of working students are proposed.